(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: Leprosy has been a literal scourge through the history of humanity and to eradicate the disease from high endemic countries need leprosy services to be sustained and they remain of good quality. Objective: The present study aimed for getting a reasonable impression of the clients views on a range of quality aspects of leprosy services rendered by district leprosy control unit under national leprosy eradication programme(NLEP). Methodology: Cross- sectional study was conducted in Satara district of western Maharashtra, India among registered leprosy patients under district leprosy control unit during April -July2008. A sample of 25 % of registered leprosy cases were selected by random sampling method from primary health centers and urban leprosy control units to assess the patients satisfaction under the functioning of NLEP. After verbal consent, participants were interviewed at home site using pre-tested structured proforma include socio -demographic and patient satisfaction variables. Data collected was compiled and analyzed by using statistical software. Results: Patients overall level of satisfaction was very good i.e. 88.89% with max, 46.03% cases were from age group 35 to 52 years. Max, 47.61% cases were illiterate with high case detection rate, 52.38% was seen males. The proportion of multi-bacillary (MB) and pauci-bacillary (PB) cases was 65.07 % & 34.92 % respectively. Most of the patients were satisfied with anti-leprosy drugs, health education and no physical deformity due to disease underline. 98.41 % patients were satisfied about follow- up and motivation services. Satisfaction about diagnosis of disease by doctors and starting of treatment was 96.82 % and 95.23 % respectively, however satisfaction with rehabilitative services was 14.28%. Significant statistical association was existed between age of leprosy affected cases and their level of satisfaction under NLEP services (?2=15.92,p <0.05*). Conclusion: Elimination of leprosy and very good patient satisfaction towards leprosy services in Satara district indicates successfulness of NLEP. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 305-309 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15430